Zambia: Systematic analysis of domestic production and world market shocks - Mukashov, Askar; Diao, Xinshen; Jones, Eleanor; Thurlow, James (International Food Policy Research Institute, 2024)
This study explores Zambia’s vulnerability to economic shocks and identifies those contributing most to economic uncertainty. The Zambian Computable General Equilibrium (CGE) model was employed to simulate a range of potential economic outcomes under various sampled shock scenarios developed using historical data on domestic agricultural yield volatilities and world market prices for traded goods. Data mining and machine learning methods were applied to quantify the contribution of each shock to the uncertainty of these outcomes. We find that Zambia’s economy is predominantly exposed to external risks, with foreign capital flows and world market price volatility together accounting for approximately three-fourths of potential variations in GDP, private consumption, poverty, and undernourishment. Domestic agricultural yield volatilities contribute the remaining one-fourth. The current struc-ture of the Zambian economy underpins these results. While agriculture is the most uncertain sector, its relatively small contribution to GDP limits its economywide and macroeconomic impacts. Instead, export earnings from cop-per and foreign exchange capital flows play a much more significant role in shaping Zambia's economic risks and their social and economic impacts. Understanding how potential shocks might impact various segments of the Zambian economy and population is a critical first step in facilitating a discussion on risk mitigation strategies that include increasing sectoral productivity or diversifying production to reduce reliance on high-risk sectors.